2020
DOI: 10.1177/0018578720985428
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clinical Pharmacist Interventions in Prescribing Errors in Hospitalized Diabetic Patients with Major Polypharmacy

Abstract: Background: While clinical pharmacists are expected to have a potential role in minimizing prescribing errors (PEs) in patients with diabetes, the effectiveness of their interventions on the incidence and clinical significance of PEs remains unclear. Objectives: To investigate the effectiveness of clinical pharmacist interventions in correcting PEs in diabetic patients with major polypharmacy. Methods: This was a prospective pre-post study conducted in a secondary care hospital in Jordan over 4 months. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
2
0
2
Order By: Relevance
“…Nevertheless, several authors have established a link between the prevention of PEs and improved pharmacological outcomes. 40,41 Second, the participants of the study self-reported the outcome measures, which might have incorporated some reporting bias, influencing the validity of the outcome assessment process. Nonetheless, direct observation was not a feasible technique to report the study outcomes given the COVID-19 situation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several authors have established a link between the prevention of PEs and improved pharmacological outcomes. 40,41 Second, the participants of the study self-reported the outcome measures, which might have incorporated some reporting bias, influencing the validity of the outcome assessment process. Nonetheless, direct observation was not a feasible technique to report the study outcomes given the COVID-19 situation.…”
Section: Discussionmentioning
confidence: 99%
“…Привлечение клинического фармаколога в качестве эксперта по безопасности ЛС в команду по лечению ожирения с нарушениями углеводного обмена может способствовать раннему выявлению и предотвращению серьезных исходов, связанных с ошибками в назначениях ЛС. Мероприятия по содействию рациональной фармакотерапии должны быть нацелены, главным образом, на людей с сопутствующими заболеваниями и полипрагмазией, которые наиболее уязвимы к НПР [38,50]. Проспективное исследование, проведенное Abu-Naser D. и соавт.…”
Section: пути преодоления использования потенциально нерациональной т...unclassified
“…Неправильная доза препарата была наиболее распространенной ошибкой (25,0%), за ней следовали назначение неправильного препарата (18,8%) и нежелательное лекарственное взаимодействие (11,5%). Таким образом, клинические фармакологи оптимизируют медикаментозную терапию и тем самым способствуют улучшению состояния здоровья [50]. Следовательно, чтобы избежать ошибок в терапии и неоправданного назначения огромного количества ЛС, врач должен хорошо понимать механизмы действия сахароснижающих ЛС.…”
Section: пути преодоления использования потенциально нерациональной т...unclassified
“…Prescription errors are clinically meaningful errors that occur when prescribing decisions or formulary processes, resulting in an unintentional and significant decrease in the probability of timely and effective treatment or an increased risk of harm compared to generally accepted practice ( Abdel-Qader et al, 2010 ) and can occur in daily clinical practice ( Bates et al, 1995 ; Noguchi et al, 2016 ). Therefore, preventing prescription errors is essential for hospitals, and hospital pharmacists play a vital role in comprehensively intervening in patient care to prevent adverse drug events (ADEs) ( Nester and Hale, 2002 ; Bond and Raehl, 2007 ; Abu-Naser, 2021 ).…”
Section: Introductionmentioning
confidence: 99%